Positive and Negative Impact of Direct Election Towards Public Service in Indonesia - Dyah Mutiarin (2012)
this papre will wxplore and describe the positive and negative impact of the direct election, since the direct election would provide more opportunities for the public to get the Regional Head in terms of accountability